Changes in Mastery Goals in Urban and Rural Middle School Students - Tierra M. Freeman (Journal of Research in Rural Education, 2005)
Little is known about differences in middle school students' motivation and the motivational climate provided across rural and urban settings. We examined change in middle school students' personal mastery goals and perceptions of mastery goal structures in their classes. Results showed students' personal mastery goals and perceptions of mastery goal structures increased over time. Rural students, as compared to urban students, reported a sharper increase in personal mastery goals. Seventh-grade mastery goals were not completely explained by students' 6th-grade mastery goals or perceptions of classroom mastery goal structures; therefore, we examined contextual data from teachers, principals, and direct classroom observations. The importance of a stable and orderly environment, at both the school and classroom levels, is highlighted.